Farmers' coping strategies against an aggregate shock: Evidence from the 2008 Sichuan Earthquake - Jin, Ling; Chen, Kevin Z.; Yu, Bingxin; Filipski, Mateusz J. (2015)
While rural households in developing countries deploy a series of risk coping strategies to insulate against shocks, their effectiveness relies heavily on the nature of the shocks. Using unique datasets collected before and after the disastrous 2008 Sichuan earthquake, this paper examines the effectiveness of various coping strategies employed by the affected rural households. The rural household survey identifies a number of coping strategies including depleting savings, government aid, subsidized bank loans, informal credit, private transfer, selling assets, and saving money by letting children drop out of school. Difference-in-differences (DID) estimation results show that, in response to the earthquake, rural households also adjust their income generating strategies through crop diversification and pursuing nonagricultural selfemployment, and increased working time by male household members. Jin, Ling; Chen, Kevin Z.; Yu, Bingxin; Filipski, Mateusz